(untitled) (American Journal of Research in Humanities and Social Sciences, 2023)
The XXI century is a period of human progress in the field of science and technology, which has reached the highest levels of all times. Many of the tasks that used to be done by human hands are now being accomplished through semi- and fully robotic technology. The article discusses the problems of paying attention to principles of time and space in the theory and practice of education.